Effect of corneal parameters on measurements using the pulsatile ocular blood flow tonograph and Goldmann applanation tonometer. Issue 4 (18th March 2004) - Gunvant, P; Baskaran, M; Vijaya, L; Joseph, I S; Watkins, R J; Nallapothula, M; Broadway, D C; O'Leary, D J
Abstract : Aims: To investigate the effect of central corneal thickness and corneal curvature on intraocular pressure measurements using the pulsatile ocular blood flow tonograph and the Goldmann applanation tonometer, and to assess the agreement between the pulsatile ocular blood flow tonograph and the Goldmann applanation tonometer in intraocular pressure measurement. Methods: 479 subjects underwent intraocular pressure measurements with the Goldmann applanation tonometer and the pulsatile ocular blood flow tonograph. Of these, 334 patients underwent additional measurement of central corneal thickness with an ultrasonic pachymeter and corneal curvature measurement with a keratometer. Results: The intraocular pressure measurements obtained with both the Goldmann applanation tonometer and the pulsatile ocular blood flow tonograph varied with central corneal thickness and mean keratometric reading. Intraocular pressure measured using the Goldmann applanation tonometer increased by 0.027 mm Hg per µm increase in central corneal thickness. Intraocular pressure measured using the pulsatile ocular blood flow tonograph increased by 0.048 mm Hg per μm increase in central corneal thickness. For an increase of 1 mm of mean corneal curvature there was rise in intraocular pressure of 1.14 mm Hg measured by the Goldmann applanation tonometer and of 2.6 mm Hg measured by the pulsatile ocular blood flow tonograph. When compared to the Goldmann applanation tonometer, the pulsatile ocular blood flow tonograph underestimated at low intraocular pressure and overestimated at higher intraocular pressure. Conclusion: Central corneal thickness and corneal curvature affected measurements obtained with the pulsatile ocular blood flow tonograph more than they affected measurements obtained with the Goldmann applanation tonometer.